Lei e ordem econômica no pensamento de John R. Commons - Guedes, Sebastião [UNESP] (Editora 34, 2013)
The paper has analyzed John R. Commons' contribution to the comprehension of Law and Economics relationship. In contrast to the orthodox economics, Commons has shown that the capitalist economic order emerges and functions regulated by laws and institutions. These approaches made possible to him to understand the nature of the modern capitalist wealth and the problems that time introduces in economic transactions.
Law and economic order in John R. Commons thought
Keywords: institutional economics; law and economics; regulated order